Revisiting the guidelines for ending isolation for COVID-19 patients - Yong Dam Jeong; Keisuke Ejima; Kwang Su Kim; Shoya Iwanami; Ana I Bento; Yasuhisa Fujita; Il Hyo Jung; Kazuyuki Aihara; Koichi Watashi; Taiga Miyazaki; Takaji Wakita; Shingo Iwami; et al. (eLife, 2021)
Since the start of the COVID-19 pandemic, two mainstream guidelines for defining when to end the isolation of SARS-CoV-2-infected individuals have been in use: the one-size-fits-all approach (i.e. patients are isolated for a fixed number of days) and the personalized approach (i.e. based on repeated testing of isolated patients). We use a mathematical framework to model within-host viral dynamics and test different criteria for ending isolation. By considering a fixed time of 10 days since symptom onset as the criterion for ending isolation, we estimated that the risk of releasing an individual who is still infectious is low (0–6.6%). However, this policy entails lengthy unnecessary isolations (4.8–8.3 days). In contrast, by using a personalized strategy, similar low risks can be reached with shorter prolonged isolations. The obtained findings provide a scientific rationale for policies on ending the isolation of SARS-CoV-2-infected individuals.